Application of Ultrasound-Guided Ilioinguinal/Iliohypogastric Nerve Block in Pediatric Same-Day Surgery - Yang, Lihua (Indian J Surg, 2015)
The aim of this study was to evaluate the safety and efficacy of ultrasound-guided ilioinguinal/iliohypogastric nerve block (IINB) in pediatric patients undergoing same-day inguinal region surgery. Ninety patients aged 4–6 years, ASA levels I–II, were randomly divided into three groups: U, T, or C (n = 30 each). After basic anesthesia, patients in group U underwent ultrasound-guided IINB, those in group T underwent traditional Schulte-Steinberg IINB, and those in group C (controls) received intravenous anesthesia (ketamine-propofol) only. Patients who remained sensitive to intraoperative stimuli received additional intravenous doses of 1 mg/kg ketamine. Heart rate (HR), mean arterial pressure (MAP), and oxygen saturation (SPO(2)) were recorded upon entering the operating room (T0), at skin incision (T1), while pulling the hernia sac (T2), during skin closing (T3), and upon awakening (T4) at recovery. HR and MAP at T1, T2, and T4 were higher in group C than those in the other two groups, and recovery time in group C was significantly prolonged (P < 0.05). Group U required significantly lower quantities and frequency of ketamine injection, and pain scores in group U during awakening were lower than those in the other two groups (P < 0.05). Ultrasound-guided IINB provided an improved nerve block effect and postoperative analgesia, reduced the amount of local anesthetic required, facilitated more rapid postoperative recovery, and was a safe and effective method of anesthesia.